High hydrostatic pressure effects on Listeria monocytogenes and L. innocua: Evidence for variability in inactivation behaviour and in resistance to pediocin bacHA-6111-2. (June 2017) - Bruschi, Carolina; Komora, Norton; Castro, Sónia Marília; Saraiva, Jorge; Ferreira, Vânia Borges; Teixeira, Paula
Abstract: The effect of high hydrostatic pressure (HHP) on the survival of 14 strains of Listeria monocytogenes from food or clinical origins, selected to represent different pheno and genotypes, was evaluated. Stationary phase cells were submitted to 300, 400 and 500 MPa at 10 °C, for 5 min. A high variability in the resistance of L. monocytogenes to pressure was observed, and particularly two strains isolated from food were significantly more baroresistant than the rest. Strains of L. monocytogenes resistant to one or more antibiotics exhibited significantly higher levels of survival after the high pressure treatment at 400 MPa. No correlation was found between strains' origin or thermal tolerance and resistance to HHP. The suitability of two strains of L. innocua as surrogates of L. monocytogenes, was also investigated. These exhibited significantly higher sensitivities to HHP than observed for some L. monocytogenes . The antimicrobial effect of the antilisterial bacteriocin (bacHA-6111-2) increased after L. monocytogenes cells had been exposed to pressure. The data obtained underlines the importance of strain selection for studies aiming to evaluate HHP efficacy to ensure safety of HHP-treated foods. Highlights: A high variability in Listeria survival to different HPP treatments was observed. Two L. monocytogenes were significantly more resistant than the other strains. Antibiotic resistant strains were more resistant to pressure treatment at 400 MPa. A pediocin enhanced antilisterial activity against pressure treated cells.